Positional parameters of EMGfor upper limb amputations / Abdirahman Hadi Omar - Abdirahman, Hadi Omar (2018)
The human hand is a remarkable creature, which facilitating many uses in our daily life activity (ADLs). A person who has lost a part of his upper limb is called amputee. Amputation is removal of limb caused by variety of reasons which include severe traumatic injuries, surgery and accidents by car or mostly by motorcycle. Different type of amputation occurs including transhumeral and transradial amputation. Myoelectric prosthesis is artificial limb (uses electromyographic (EMG) signal) used to restore the function of removal limb using muscle activity from the remaining limb for the control of prosthesis device. One of the challenges facing the myoelectric prosthesis is the position of EMG sensor which static inside the socket and sometimes attached to the non-active muscle, resulting inefficiency prosthetic limb function. The aim of this study is to investigate the positional parameters of EMG for transradial prosthetics users by finding the strongest detectable position outside the socket and to compare it with normal human activities. DELSYS Trigno wireless EMG instrument was used in this study to achieve this goal. Ten normal subjects and two subjects with transradial amputees were involved in this study. Two wireless EMG sensor and four different locations from upper limb muscles were selected. Two different tests were performed. The first test, two muscles were selected from upper arm muscles (biceps and triceps muscles) where two EMG sensors were placed respectively. Three different activities were performed during this test which are muscle strength, flexion and extension and flexion and extension with 5kg weight. Muscles selected for the second test were extensor carpi ulnaris (ECU) muscle and Brachioradialis muscle from the forearm muscles and repeated the same activities. The study found that during all the activities, upper arm muscles were performed better EMG activity than forearm muscles for the both transradial amputees and normal subjects. Biceps muscles have demonstrated the strongest muscle that showed the highest value of EMG signal. Based on the results, the study suggests that EMG sensor should be placed outside the socket so that to be adjustable and for user’s convenience to control the myoelectric prosthesis.